Orthographic, Phonetic and Grammatical Aspects in José Miguel Carrera’s Manuscripts, a Chilean Pro-Independence Forefather - Almau Almau, Sonia (2023)
This paper analyzes the most significant orthographic, phonetic and grammatical aspects of two manuscripts written by J. M. Carrera, who was an illustrious forefather of Chilean Independence. Through his scripts –his large Diario Militar (1810-1814) and his Libreta (that he left before dying executed)– we can discover not only a tumultuous period, but also an evolving language. These texts show linguistic aspects due to diachrony and innovative linguistic features, which are characteristic of South American Spanish.